Pathogen clearance and immune adherence "revisited": Immuno-regulatory roles for CRIg. (June 2018) - van Lookeren Campagne, Menno; Verschoor, Admar
Highlights: CRIg is a complement-receptor and -regulator impacting innate and adaptive immunity. CRIg-expression is associated with homeostatic, non-inflammatory processes. Cooperation between immune adherence and CRIg is critical to resolve bacteremia. CRIg regulates distribution of systemic bacteria to phagocytes in liver and spleen. CRIg has an immune-modulatory role in cancer, autoimmuntiy and infection. Abstract: Rapid elimination of microbes from the bloodstream, along with the ability to mount an adaptive immune response, are essential for optimal host-defense. Kupffer cells are strategically positioned in the liver sinusoids and efficiently capture circulating microbes from the hepatic artery and portal vein, thus preventing bacterial dissemination. In vivo and in vitro studies have probed how complement receptor of the immunog lobulin superfamily (CRIg), also referred to as Z39Ig and V-set and Ig domain-containing 4 (VSIG4), acts as a critical player in pathogen recognition and clearance. While recent data suggested that CRIg may bind bacterial cell wall components directly, the single transmembrane receptor is best known for its interaction with complement C3 opsonization products on the microbial surface. On Kupffer cells, CRIg must capture opsonized microbes against the shear forces of the blood flow. In vivo work reveals how immune adherence (IA), a process in which blood platelets or erythrocytes associate with circulating bacteria, plays a critical role in regulating pathogen capture by CRIg under flow conditions. In addition to its typical innate immune functions, CRIg was shown to directly and indirectly influence adaptive immune responses. Here, we review our current understanding of the diverse roles of CRIg in pathogen elimination, anti-microbial immunity and autoimmunity. In particular, we will explore how, through selective capturing by CRIg, an important balance is achieved between the immunological and clearance functions of liver and spleen.